Success Factors for Road Management Systems - McPherson, Kevin; Bennett, Christopher R. (World Bank, Washington, DC, 2012)
Over the last 20 years most road agencies have implemented some form of computerized road management system (RMS). The purpose of these systems is to assist the road agency in the planning and prioritization of road investments. While some systems have been successful, there have also been many which have failed in one or more areas. This is in spite of large investments of time and money. While it is often easy to identify the symptoms of failure, the causes are often complex and multi-layered. However, for every failed system, there is a more successful implementation somewhere in the world, in an agency that often suffers from similar problems and constraints. This Note describes the different factors associated with successful RMS implementations. It is a summary of the report Success Factors for Road Management Systems.